The oriental question under the July Monarchy - (:unkn) unknown (My University, 2004)
In 1830, Greece became independent. The Ottoman empire with his numerous nationalities was in crisis. Moribund Turks were drived away from Algeria. This victory did not save the power of Charles X. After the July Revolution, Louis-Philippe had to continue the conquest. French fought Abd el-Kader and the bey of Constantine. From Egypt, Muhammad Ali pasha wanted to replace the current Ottoman Sultan Mahmud II. War in Middle East took place in 1832-1833 and in 1839-1840. The battle at Nezib (24th june 1839) sounded the death knell of "the Sick Old Man". According to Lamartine "Ottoman Empire is like an empty turban." To extinguish the blaze, to defend their interests, to protect the trade routes, to ensure safety for christians and anxious to maintain European balance, powerful nations involved. Those arms wrestling used spies, diplomacy, gunboat policy and land armies. Russia threatened central Asia, Persia, Caucasus and Constantinople. Feeling attacked near India, Great-Britain sent Royal Navy to the syria coasts and the red coats invaded Afghanistan. And France pruned to the lion's share in North Africa. Duke of Aumale took smala Abd el-Kader May 16, 1843. Bugeaud defeated the Moroccans Isly August 14, 1844. The colonization of Algeria allowed the July Monarchy to revive the Roman civilization. African lobby was powerful but at the time of the revolution of 1848, there is no place for an overseas chouannerie Orleanist.
Keywords: African Research